Inertial Oscillations and Frontal Processes in an Alboran Sea Jet: Effects on Divergence and Vertical Transport. Issue 3 (25th February 2023) - Esposito, Giovanni; Donnet, Sebastien; Berta, Maristella; Shcherbina, Andrey Y.; Freilich, Mara; Centurioni, Luca; D'Asaro, Eric A.; Farrar, J. Thomas; Johnston, T. M. Shaun; Mahadevan, Amala; Özgökmen, Tamay; Pascual, Ananda; et al.
Abstract: Vertical transport pathways in the ocean are still only partially understood despite their importance for biogeochemical, pollutant, and climate applications. Detailed measurements of a submesoscale frontal jet in the Alboran Sea (Mediterranean Sea) during a period of highly variable winds were made using cross‐frontal velocity, density sections and dense arrays of surface drifters deployed across the front. The measurements show divergences as large as ± f implying vertical velocities of order 100 m/day for a ≈ 20 m thick surface layer. Over the 20 hr of measurement, the divergences made nearly one complete oscillation, suggesting an important role for near‐inertial oscillations. A wind‐forced slab model modified by the observed background frontal structure and with initial conditions matched to the data produces divergence oscillations and pattern compatible with that observed. Significant differences, though, are found in terms of mean divergence, with the data showing a prevalence of negative, convergent values. Despite the limitations in data sampling and model uncertainties, this suggests the contribution of other dynamical processes. Turbulent boundary layer processes are discussed, as a contributor to enhance the observed convergent phase. Water mass properties suggest that symmetric instabilities might also be present but do not play a crucial role, while downward stirring along displaced isopycnals is observed. Plain Language Summary: Vertical transport pathways are essential for the exchange of properties between the surface and the deeper layers of the ocean. Despite the recognized role of vertical dynamics in biogeochemical and climate applications, it is still only partially understood. This is principally due to observational challenges. Vertical transport pathways are generally very localized processes and are associated with vertical velocities comparable to instrumental uncertainty. In this work, we focus on vertical processes occurring along a front at the edge of an eddy in the Mediterranean Sea. The paper combines the analysis of multiple observations with the use of an idealized numerical model to isolate and study surface divergence patterns. These analyses allow the investigation of the role of the wind forcing and of small‐scale ocean processes in vertical transport. Key Points: Divergence and vertical velocity oscillations are observed at a submesoscale front on the edge of an anticyclone in the Alboran Sea Near‐inertial oscillations play a major role in the observed divergence oscillatory pattern as suggested by a modified slab model of a wind‐forced frontal jet Turbulent boundary layer processes and symmetric instabilities can contribute to differences between modeled and observed vertical dynamics